Prevalence and clinical profile of rotavirus in children ? 5 years admitted in a tertiary care Hospital in Western Maharashtra - Aundhakar, Chandrashekhar D; Gupta, Ankit; Mishra, Lekha; Karande, Geeta Satish; Karande, Priyanka (Indian Journal of Community Health, 2017)
Background: Diarrhea is the second leading cause of mortality in children less than 5 years. Rotavirus is the commonest pathogen which causes diarrhea in children. As a result of dehydration and its hazardous consequences, it causes various deleterious effects on a child resulting in growth failure and malnutrition and sometimes leading to death. Aims & Objectives: To determine the prevalence and elucidate the clinical pattern of rotavirus diarrhea and differentiate it from non-rotavirus diarrhea in children ? 5 years hospitalized for acute diarrhea. Material & Methods: It was a cross-sectional study carried out between October 2014 and September 2016 on a total of 189 patients admitted for acute diarrhea in a tertiary care hospital. Stool samples were processed for identification of rotavirus antigen by ELISA. Clinical characteristics along with the seasonal variation of the infection were also studied. Result: Prevalence of rotavirus in the present study was estimated to be 36.5%. Infection occurred mostly in the age group of 7 – 12 months (46.3%) followed by 1 – 6 months (31.8%). Positive cases had associated clinical features as vomiting (69.5%), fever (55%) and peri-anal redness (33.3%). Maximum no. of rotavirus cases occurred in the winter season (42%). Conclusion: Rotavirus diarrhea does not follow a specific clinical pattern and lead to substantial morbidity in the study population.